Investigating Leadership Dynamics: A Comparative Analysis of Situational Leadership Theory and Contemporary Leadership Practices in a Public School - Khaleel, Badriah; Kausar, Shahida; Riaz, Sumiya (Annals of Human and Social Sciences, 2024)
This study aims to investigate leadership dynamics in a public school setting through a comparative analysis of Situational Leadership Theory (SLT) and contemporary leadership practices. The research focuses on understanding how adaptive leadership approaches can enhance teacher motivation and achievement levels. Principals play a crucial role in shaping the school environment, including fostering a conducive learning atmosphere, managing resources effectively, and boosting teacher morale. The methodology involves qualitative exploration and description, utilizing systematic observation and reflection to evaluate leadership behaviors. Results indicate the importance of principals adapting their leadership styles to meet the changing needs of teachers and students throughout the academic year, ultimately supporting academic growth and achievement. The study concludes that effective leadership in public schools requires a flexible approach that balances directive, coaching, supporting, and delegating styles based on situational demands. Recommendations include providing targeted training for principals to enhance their application of SLT and modern leadership practices for improved school performance.